Measurement of blood flow in pancreatic exchange capillaries with FITC-labeled erythrocytes - Mithöfer, Kai; Schmidt, Jan; Gebhard, Martha-Maria; Buhr, Heinz J.; Herfarth, Christian; Klar, Ernst (Microvascular research, 1995)
Characterization of pancreatic capillary blood flow by in vivo microscopy has been limited by technical shortcoming associated with the use of plasma tracers and the lack of quantitative data. Therefore, fluorescent-labeled erythrocytes were evaluated for quantitation of pancreatic capillary blood flow in rats in physiological state and under defined conditions of increased and impaired pancreatic blood flow. Physiological blood flow was 1.21 ± 0.06 nl/min per capillary with stable capillary perfusion pattern. Reduction of pancreatic blood flow by decreasing systemic arterial pressure to 60 mm Hg through controlled hemorrhage produced a profound decrease of volumetric flow to 0.21 ± 0.05 nl/min (P < 0.05). The number of perfused capillaries was reduced to 52 ± 8% of baseline (P < 0.001) and the intermittent perfusion pattern was altered in 26 ± 5% (P < 0.001) of observed capillaries. Stimulation of pancreatic perfusion with intravenous secretin (5 CU/kg/hr) induced a transient decline to 0.94 nl/min (P < 0.05) followed by a continuous increase to 2.39 nl/min (P < 0.001). The intermittent flow pattern was modified in 15 ± 3% of capillaries (P < 0.05). Fluorescent-labeled erythrocytes provide unique and reliable qualitative and quantitative data about pancreatic microcirculatory changes. Confinement of the fluorescent tracer to erythrocytes prevents extravasation and minimizes phototoxicity, thereby improving intravital analysis of blood flow in pancreatic exchange capillaries.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Gesehen am 25.09.2025